2015
DOI: 10.1177/2050640614560453
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of the 5‐HT1A receptor agonist buspirone on esophageal dysfunction associated with systemic sclerosis: A pilot study

Abstract: Background: Esophageal involvement in systemic sclerosis (SSc) carries significant morbidity and is empirically managed with domperidone, albeit with questionable efficacy. The oral 5-HT 1A receptor agonist buspirone may enhance esophageal peristalsis and lower esophageal sphincter (LES) function in healthy volunteers. Aim: We aimed to test the hypothesis that buspirone may exert a beneficial acute effect on esophageal motor dysfunction in symptomatic patients with SSc. Methods: Twenty consecutive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
0
28
0
1
Order By: Relevance
“…Nevertheless, studies are looking into their use to treat esophageal motility disorders (Karamanolis et al, ; Scheerens et al, ), gastroesophageal reflux disorders (Ostovaneh et al, ), and hypersensitive esophagus (Viazis et al, , ; Dickman et al, ). Recent research analyzing the effectiveness of the serotonin agonist Buspirone in the treatment of esophageal dysfunction associated with systemic sclerosis demonstrated an increase in esophageal motility in 30 patients (Karamanolis et al, ). Other investigations inspired by this study tested greater levels of Buspirone, among other similar compounds, and found that serotonin agonists produce enough effect to warrant greater study and consideration (Scheerens et al, ).…”
Section: Neurotransmitters and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies are looking into their use to treat esophageal motility disorders (Karamanolis et al, ; Scheerens et al, ), gastroesophageal reflux disorders (Ostovaneh et al, ), and hypersensitive esophagus (Viazis et al, , ; Dickman et al, ). Recent research analyzing the effectiveness of the serotonin agonist Buspirone in the treatment of esophageal dysfunction associated with systemic sclerosis demonstrated an increase in esophageal motility in 30 patients (Karamanolis et al, ). Other investigations inspired by this study tested greater levels of Buspirone, among other similar compounds, and found that serotonin agonists produce enough effect to warrant greater study and consideration (Scheerens et al, ).…”
Section: Neurotransmitters and Diseasesmentioning
confidence: 99%
“…• Administration of SRI's and serotonin agonists has shown some success in the treatment of esophageal motility disorders. Karamanolis et al (2015) and Scheerens et al (2015) Hypersensitive esophagus…”
Section: Depressionmentioning
confidence: 99%
“…Withdrawing muscle relaxant medications as a first‐line treatment for patients with IEM may improve esophageal motility, but it remains unclear if symptom improvement will follow suit. Buspirone and Bethanechol have been commonly used to treat IEM, based on studies demonstrating an effect on objective swallowing parameters, but neither has been shown to have an effect on esophageal symptoms . Overall, our therapeutic approach to some of the esophageal motor disorders has been based on improving objective parameters, in the hope that subjective parameters like patients’ symptoms will improve as well.…”
Section: Discussionmentioning
confidence: 99%
“…102,108 In a study published in 2015, buspirone improved LES pressure but not oesophageal contractile amplitude in a cohort of patients with dysphagia and systemic sclerosis. 109 Long-term clinical studies and studies in other hypomotility disorders are needed to evaluate whether this drug has any potential benefit. Finally, addition of capsaicin to the bolus was reported to enhance peristaltic amplitude, 110 but there are several hurdles to its use for dysphagia in clinical practice.…”
Section: Oesophageal Hypomotility Disordersmentioning
confidence: 98%